Association Study for 26 Candidate Loci in Idiopathic Pulmonary Fibrosis Patients from Four European Populations - Kishore, Amit; Žižková, Veronika; Kocourková, Lenka; Petrkova, Jana; Bouros, Evangelos; Nunes, Hilario; Loštáková, Vladimíra; Müller-Quernheim, Joachim; Zissel, Gernot; Kolek, Vitezslav; Bouros, Demosthenes; Valeyre, Dominique; et al. (Frontiers in Immunology, 2016)
Idiopathic pulmonary fibrosis (IPF) affects lung parenchyma with progressing fibrosis. In this study, we aimed to replicate MUC5B rs35705950 variants and determine new plausible candidate variants for IPF among four different European populations. We genotyped 26 IPF candidate loci in 165 IPF patients from four European countries: Czech Republic (n = 41), Germany (n = 33), Greece (n = 40), France (n = 51) and performed association study comparing observed variant distribution with this obtained in a genetically similar Czech healthy control population (n = 96) described in our earlier data report. A highly significant association for a promoter variant (rs35705950) of mucin encoding MUC5B gene was observed in all IPF populations, individually and combined [OR (95% CI); p-value as 5.23 (8.94-3.06); 1.80x10-11). Another non-coding variant, rs7934606 in MUC2 was significant among German patients [2.85 (5.05-1.60); 4.03x10-4] and combined European IPF cases [2.18 (3.16-1.50); 3.73x10-5]. The network analysis for these variants indicated gene-gene and gene-phenotype interactions in IPF and lung biology. With replication of MUC5B rs35705950 previously reported in U.S. populations of European descent and indicating other plausible polymorphic variants relevant for IPF, we provide additional reference information for future extended functional and population studies aimed, ideally with inclusion of clinical parameters, at identification of IPF genetic markers.